Design of tandem solar cell to enhance the conversion efficiency using FDTD simulation - Patwary, Al-Amin; Feroz, Mohammad Ahmed; Saif, Salik Bin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.